Heat and mass transfer effects on an unsteady mhd flow of a rotating fluid past a vertical porous plate - G Murali; E.M. Reddy; Narepalepu Venkata N. B (International Journal of Science and Engineering, 2015)
An attempt is made to investigate the heat and mass transfer effects on an unsteady free convection flow of a rotating, incompressible, viscous Boussinesq fluid in presence of first order chemical reaction. The governing dimensionless equations for this investigation are solved numerically by a finite element method. A parametric study illustrating the influence of different flow parameters on velocity, concentration and temperature are investigated. Also the Skin – friction, Nusselt number and Schmidt number are shown through tabular forms. Numerical results are presented for various parameters.